2005
DOI: 10.1029/2004jb003386
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb stress changes caused by repeated normal faulting earthquakes during the 1997 Umbria‐Marche (central Italy) seismic sequence

Abstract: We investigate fault interaction through elastic stress transfer among a sequence of moderate‐magnitude main shocks (5 < Mw < 6) which ruptured distinct normal fault segments during a seismic sequence in the Umbria‐Marche region (central Apennines). We also model the spatial pattern of aftershocks and their faulting mechanisms through Coulomb stress changes. We compute stress perturbations caused by earthquake dislocations in a homogeneous half‐space. Our modeling results show that seven out of eight main shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 39 publications
12
61
0
1
Order By: Relevance
“…Nostro et al (2005) showed that this approach provides similar results with the isotropic poroelastic model (Beeler et al 2000;Cocco and Rice 2002). According to this model, the pore pressure changes depend on the volumetric stress changes such that DP = -BDr kk /3.…”
Section: Coulomb Stress Changessupporting
confidence: 51%
“…Nostro et al (2005) showed that this approach provides similar results with the isotropic poroelastic model (Beeler et al 2000;Cocco and Rice 2002). According to this model, the pore pressure changes depend on the volumetric stress changes such that DP = -BDr kk /3.…”
Section: Coulomb Stress Changessupporting
confidence: 51%
“…Five out of six earthquakes occurred in areas of enhanced Coulomb stress by previous main shocks [Cocco et al, 2000;Nostro et al, 2005] showing evidences that the spatial pattern of seismicity is consistent with elastic stress interaction. However, the temporal evolution of seismicity shows a peculiar pattern: seismicity migrated and activated the southernmost main fault plane before the occurrence of its impending mainshock .…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several features make the study of this sequence particularly interesting: (1) earthquakes were located with the double-difference and cross-correlation technique and the resulting errors are of the order of tens of meters [Chiaraluce et al, 2003]; (2) seismicity migrated toward the SE-direction progressively activating the main fault planes before the occurrence of their impending mainshocks ; (3) other [Nostro et al, 2005], but it cannot explain the presence of seismicity in the hanging wall of the main faults [Miller et al, 2004] as well as the temporal migration of seismic events; (4) there are evidence of the presence of fluids in this area [Chiodini et al, 2000]. All these factors motivate our study.…”
Section: The Seismic Sequencementioning
confidence: 99%
“…Coulomb stress triggering of moderate-to-large earthquakes has been observed in the US [4,[11][12][13], in Europe [14][15][16], on the Sunda Trench [17][18][19], and in Japan [20][21][22][23][24][25]. However, in South America and Ecuador, the stress triggering theory has yet to be extensively studied [26][27][28].…”
Section: Introductionmentioning
confidence: 99%